Perspectives on precision cut lung slices—powerful tools for investigation of mechanisms and therapeutic targets in lung diseases - Lam, Maggie; Lamanna, Emma; Organ, Louise; Donovan, Chantal; Bourke, Jane E. (Frontiers in Pharmacology, 2023)
Precision cut lung slices (PCLS) have emerged as powerful experimental tools for respiratory research. Pioneering studies using mouse PCLS to visualise intrapulmonary airway contractility have been extended to pulmonary arteries and for assessment of novel bronchodilators and vasodilators as therapeutics. Additional disease-relevant outcomes, including inflammatory, fibrotic and regenerative responses, are now routinely measured in PCLS from multiple species, including human. This review provides an overview of established and innovative uses of PCLS as an intermediary between cellular and organ based studies, and focuses on opportunities to increase their application to investigate mechanisms and therapeutic targets to oppose excessive airway contraction and fibrosis in lung diseases.